REVITALISASI RUANG AGAMA UNTUK PERUBAHAN SOSIAL PADA MASYARAKAT SIDOREJO MAGETAN - Ahmad Taufiqurrohman; Ninik Rohani (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2024)
social changes happens in the society cannot read of the positive and negative effect, so it needs an orientation and guidance that can lead human do their role in the social changes in the society. In this case, the role of religious becomes very important. In the social interection, the exsistence of progress influences the society’s behaviour and attitude, so that there are many diverged behaviour in the society that can desturb the society’s stability. By a continuous and sustainable actualization of islamic values, it can show the positive social changes in the society. Besides as an orientation, islam can also be used as filter to the negative effect in the social changes in the society. The purpose is to make the society more selective in tacking and receiving the west new cultures.